2017
DOI: 10.1155/2017/2756891
|View full text |Cite
|
Sign up to set email alerts
|

OCT4B1 Regulates the Cellular Stress Response of Human Dental Pulp Cells with Inflammation

Abstract: Introduction. Infection and apoptosis are combined triggers for inflammation in dental tissues. Octamer-binding transcription factor 4-B1 (OCT4B1), a novel spliced variant of OCT4 family, could respond to the cellular stress and possess antiapoptotic property. However, its specific role in dental pulpitis remains unknown. Methods. To investigate the effect of OCT4B1 on inflammation of dental pulp cells (DPCs), its expression in inflamed dental pulp tissues and DPCs was examined by in situ hybridization, real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Previous studies indicated that OCT4B might be involved in cellular stress response and antiapoptotic activity in cancer cells . Importantly, OCT4B may indirectly be increased in dental pulp tissues and dental pulp cells exposed to proinflammatory factors, where it has been suggested that OCT4B represents a antiapoptotic mediator and subsequently may be the important factor in dental regeneration . Our results indicate that IL‐33 increases expression of OCT4B mRNA expression in both PDLSCs and DPSCs.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies indicated that OCT4B might be involved in cellular stress response and antiapoptotic activity in cancer cells . Importantly, OCT4B may indirectly be increased in dental pulp tissues and dental pulp cells exposed to proinflammatory factors, where it has been suggested that OCT4B represents a antiapoptotic mediator and subsequently may be the important factor in dental regeneration . Our results indicate that IL‐33 increases expression of OCT4B mRNA expression in both PDLSCs and DPSCs.…”
Section: Discussionsupporting
confidence: 86%
“…It has been demonstrated that OCT4B isoforms are associated with a response to oxidative and genotoxic stress, as well as with an antiapoptotic activity [51][52][53]. Here, OCT4B isoforms were shown to be faintly expressed during starvation and increased during the proliferative phase poststarvation.…”
Section: Discussionmentioning
confidence: 77%
“…LPS stimulation also upregulates octamer-binding transcription factor 4-B1 (OCT4B1) leading to overexpression of OCT4B [ 8 ]. Both particles protect hDPCs from apoptosis [ 9 ]. Silencing OCT4B1 changes the expression of 38 microRNAs [ 8 ].…”
Section: Resultsmentioning
confidence: 99%